Lessons from appropriate-scale mechanization projects across regions: Rural labour dynamics, access and scaling approaches are key issues - CGIAR Research Program on Wheat (2021)
MAIZE, WHEAT and partners developed, refined and sustained appropriate-scale mechanization solutions, linked to climate-smart practices (e.g. zero-till, rotation) in Africa, South Asia, and Latin America, which contributed to improved livelihoods and income. Research for Development focused on mitigating labour shortages and building capacity for delivery and /support systems. Research revealed a much higher demand for mechanization than previous studies had shown, indicating that access was the problem, not demand or affordability. Constraints to scaling differ across regions, but remain significant.